Painful Auras in Focal Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
The localizing and lateralizing value of painful epileptic auras in 25 patients with focal epilepsy were studied at the Cleveland Clinic, OH.